REPRODUCTIVE JUSTICE AND WOMEN’S HEALTH RIGHTS IN INDONESIA: BETWEEN LEGAL PROTECTION AND STRUCTURAL INEQUALITY - Yusrizal Hasbi; Ferdy Saputra; Hadi Iskandar; Romi Asmara (Faculty of Law, Universitas Diponegoro, 2026)
Women’s reproductive health rights constitute a fundamental component of human rights, imposing an obligation on the state to respect, protect, and fulfill women’s health rights in a fair, equal, and non-discriminatory manner. This study aims to analyze the legal protection of women’s reproductive health rights in Indonesia from legal and human rights perspectives, with particular reference to Law Number 17 of 2023 concerning Health and Government Regulation Number 28 of 2024. This research employs a socio-legal method with a descriptive-analytical approach, supported by library research and policy analysis. The data consist of primary, secondary, and tertiary legal materials, including statutory regulations, academic literature, human rights instruments, and relevant policy documents, which are analyzed qualitatively through deductive reasoning. The findings indicate that Indonesia has developed a relatively progressive legal framework through the strengthening of reproductive rights, the expansion of maternal healthcare services, protection against discrimination and violence, and the recognition of women’s reproductive autonomy. However, the implementation of these legal protections continues to face significant structural challenges. These include the unequal distribution of healthcare workers, limited healthcare infrastructure in remote and disadvantaged areas, socio-cultural barriers rooted in patriarchal norms, insufficient reproductive health education, and weak state accountability mechanisms in ensuring equal access to healthcare services. Furthermore, normative ambiguities concerning religious and moral values in the regulation of reproductive rights may potentially restrict women’s autonomy and create uncertainty in service delivery. The study argues that the protection of women’s reproductive health rights cannot rely solely on formal legal recognition, but must also be supported by effective implementation, institutional responsiveness, and substantive equality. Therefore, strengthening legal protection requires harmonization between national and regional policies, reinforcement of a human rights-based and gender-responsive approach, and improvement of equitable, accessible, and accountable healthcare services for women throughout Indonesia.